2017
DOI: 10.1523/jneurosci.2125-16.2017
|View full text |Cite
|
Sign up to set email alerts
|

GABAergic Interneuron Differentiation in the Basal Forebrain Is Mediated through Direct Regulation of Glutamic Acid Decarboxylase Isoforms by Dlx Homeobox Transcription Factors

Abstract: GABA is the key inhibitory neurotransmitter in the cortex but regulation of its synthesis during forebrain development is poorly understood. In the telencephalon, members of the distal-less () homeobox gene family are expressed in, and regulate the development of, the basal ganglia primodia from which many GABAergic neurons originate and migrate to other forebrain regions. The double knock-out mice die at birth with abnormal cortical development, including loss of tangential migration of GABAergic inhibitory i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
49
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 56 publications
2
49
1
Order By: Relevance
“…Dlx1 is proposed to be the founding member of the vertebrate Dlx family because it is most closely related to the Dll gene of Drosophila and amphioxus (Panganiban & Rubenstein, 2002). However, DLX2 is expressed before DLX1 during forebrain development in the mouse (Eisenstat et al, 1999;Le et al, 2017), and previously we also found that DLX2 is more robust than DLX1 as a transcriptional activator (Le et al, 2017;Q. P. Zhou et al, 2004) or transcriptional repressor (Le et al, 2007), signifying a more important role for the Dlx2 gene in forebrain development.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Dlx1 is proposed to be the founding member of the vertebrate Dlx family because it is most closely related to the Dll gene of Drosophila and amphioxus (Panganiban & Rubenstein, 2002). However, DLX2 is expressed before DLX1 during forebrain development in the mouse (Eisenstat et al, 1999;Le et al, 2017), and previously we also found that DLX2 is more robust than DLX1 as a transcriptional activator (Le et al, 2017;Q. P. Zhou et al, 2004) or transcriptional repressor (Le et al, 2007), signifying a more important role for the Dlx2 gene in forebrain development.…”
Section: Discussionsupporting
confidence: 64%
“…We have optimized our ChIP protocol to preferentially obtain homeoproteingenomic DNA complexes from embryonic tissues in situ (Q. P. Zhou et al, 2004). With the sensitive and highly specific antisera we possess (Eisenstat et al, 1999), several direct transcriptional targets of DLX1/2 proteins during forebrain development have been determined including the Dlx5/6 intergenic enhancer, neuropilin-2 and the glutamic acid decarboxylase genes Gad1/Gad2 (Le et al, 2007;Le et al, 2017;Q. P. Zhou et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study revealed pivotal roles of Dlx1 and Dlx2, members of the Dlx gene, in GABA synthesis [24]. Recently, Le et al demonstrated that Dlx1 and Dlx2 directly bind to and activate the transcription of the Gad promoters [25]. Moreover, using chromatin immunoprecipitation (ChIP) of the embryonic forebrain, they identi ed two Dlx target sequences within the Gad2 promoter regions.…”
Section: Identi Cation Of a Candidate Region For Inhibitory Neuronspementioning
confidence: 99%
“…The Dlx target regions were at nucleotide positions of -2,294 --2,088 and − 958 --598 (Region i and Region ii, respectively) ( Fig. 1A), both of which contained speci c homeodomain DNA-binding tetranucleotide TAAT/ATTA motifs [25]. Thus, these regions were postulated to be critical for the Gad2 promoter in terms of inhibitory neuron speci city as well as promoter activity.…”
Section: Identi Cation Of a Candidate Region For Inhibitory Neuronspementioning
confidence: 99%
“…ASCL1, GSX2, DLX1/2/5/6), studies with DLX1/2 knockout mice, while leading to an embryonic lethal phenotype, surprisingly still demonstrate the generation of GABAergic neurons(Le 2007). Interestingly, one study additionally found an accumulation of INs in the ganglionic eminences, though this may be due to impaired migration to the cortex rather than a proliferative effect per se(Le 2007(Le , 2017. Strengthening this hypothesis, a recent reportfrom Tasic et al utilized single-cell RNA sequencing and clustering algorithms to assess cellular diversity in the mouse visual cortex and identified 49 distinct cell types, including two novel NDNF + IN subtypes (2.61-fold upregulated with EtOH) (Tasic 2016).…”
mentioning
confidence: 99%